AN ANALYSIS DIRECTIVE ILLOCUTIONARY ACT FOUND IN “TINKERBELL AND THE LEGEND OF THE NEVERBEAST” MOVIE - Lestari, Ni Made Putri Dwi; I Wayan, Juniartha (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study aims to know and identify the meaning, types of directive illocutionary act dominantly used and also identify the conflict that found in “Tinkerbell and The Legend of The Neverbeast” movie. This analysis use descriptive qualitative method to collecting data. The data source is taken from the directive illocutionary act that used in the conversation of this movie. In collecting the data, observational method is used by conduct several technique watching the movie, identify the dialogue, identify the caterogies of directive illocutionary act by using the theory of Searle and Vanderveken (1985). It is found there are some types of directive illocutionary act found the Tinker Bell and The Legend of The Neverbeast conversation. Based on the data analysis, there are some types of directive illocutionary act found in this movie. This study shows that the dominant types of directive illocutionary act found in this movie is asking, followed by telling and ordering.